Activities in nature: how frequent is the contact of contemporary children with the natural world? - Almeida, António (2020)
The progressive process of industrialization occurring in the world in the last 200 years has increased the urban population. One of its consequences has been the gradual detachment from nature, which negatively affects children’s development. At the same time, several authors state that children play essentially indoors, and outdoor activities are declining not only in nature places but also in urban areas, due to several reasons. The present study aims to check how frequently a myriad of several outdoor activities are performed by a group of 153 urban children, 87 boys and 70 girls, from 6 state primary schools with different social backgrounds (low to high socio-economic status) from the Lisbon area. Differences between boys and girls were also analysed. For this purpose, a questionnaire was administered containing demographic-related items, such as sex, age and school, and the following 11 statements pertaining to different outdoor activities: picking up wild fruits; gardening; climbing trees; catching birds in traps; collecting rocks, minerals and fossils; tracking; visiting farms, zoos and other thematic parks; practising outdoor sports; playing in forested areas; going hunting or fishing with friends and relatives; rappelling and other extreme sports. Children had to select the frequency of their performing of each activity on a four-point scale. A total score for the 11 activities was also calculated. The results show that almost all activities have never or rarely been done by the participants, and only outdoor sports are practised more often (sometimes). Boys and girls statistically significant differences were only for practising outdoor sports and for hunting and fishing with friends and relatives, favouring boys. But the frequency of this latter activity was very low in both genders. The present study confirmed children’s prevalent disconnection with nature alongside the decline in performing different outdoor activities, showing that this trend is at least affecting several western countries. Since the situation is impoverishing children’s development and affecting their knowledge and awareness about the importance of the natural world, implications for parents, teachers and policy makers are discussed to try to invert the present trend.